I08 fMRI shows an distributed extrastriatal network of altered neural activation in premanifest Huntington's disease gene carriers. (16th November 2010) - Novak, M; Draganski, B; Henley, S; Warren, J; Frackowiak, R; Tabrizi, S J
Abstract : Background: Striatal atrophy is seen in preHD; neural dysfunction can be detected with functional MRI (fMRI) prior to this. Identification of negative emotional facial expressions is impaired in premanifest and manifest HD. We wished to assess extrastriatal neural function in preHD and hypothesised that an fMRI emotion recognition paradigm would elicit this. Aims: To assess neural function in preHDs during an emotion recognition paradigm; to elicit extrastriatal neural dysfunction and establish the mechanism of impaired emotion recognition. Methods: 14 preHDs and 16 matched controls were tested. Subjects viewed pictures of modified Ekman faces and carried out a task of classifying each face by gender while undergoing fMRI. This tested implicit recognition of facial expressions. Structural images were also acquired and analysed with VBM. The Ekman 60 test was performed outside the scanner to assess explicit emotion recognition accuracy. Probability of disease onset in 5 years (PDO) was estimated from CAG repeat length and age. Results: VBM revealed bilateral striatal volume loss only in the preHDs. FMRI analyses showed extensive altered extrastriatal activation in the preHDs for disgusted but not angry or happy faces. When the preHDs were analysed alone, significant negative correlations were found between neural activation (BOLD) and PDO. When the preHD and control group activations were compared including disgust recognition accuracy score as a regressor of interest in the model, BOLD response in regions including the insulae and superior temporal gyri correlated with accuracy score in preHDs more than controls. When the effect of emotion recognition accuracy was controlled for (regressed out of the analysis), preHDs showed reduced activation in a network including the praecuneus bilaterally and the right postcentral gyrus: preHDs have a reduced 'baseline' level of activation for emotion recognition in this network. Conclusions: A distributed extrastriatal network of neural dysfunction was elicited with emotion stimuli and was associated with impaired emotion recognition. This may have implications for the development of therapeutic drugs. The network was associated with premanifest disease progression, measured by PDO, suggesting that fMRI may have use as a biomarker of premanifest disease progression.